THE ART OF THE STAY INTERVIEW: PROACTIVE STRATEGIES TO REDUCE TURNOVER BEFORE IT STARTS - Zulkifli; Ramon Zamora; Dhenny Asmarazisa (RADJA PUBLIKA, 2026)
Employee turnover poses a significant financial and operational challenge for organizations globally, driven by factors like disengagement, poor management, and misaligned career paths. This study explores the stay interview as a proactive, relational tool to enhance retention by identifying and addressing employee concerns before they lead to resignation. Using a qualitative case study methodology, the research analyzed the implementation of a structured stay interview program within a mid-sized technology firm over 12 months. Data was collected through semi-structured interviews with managers and participating employees, alongside analysis of retention metrics. Results indicated a 25% reduction in voluntary turnover and a marked improvement in employee engagement scores. The discussion emphasizes that the efficacy of stay interviews hinges on managerial training, a culture of psychological safety, and a demonstrable follow-up on issues raised. The study concludes that integrating stay interviews into a broader talent retention strategy transforms them from a procedural task into a strategic asset for building organizational commitment and preempting turnover.